(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
According to published literature work most of the welded joints have a Lack Of Penetration (LOP) defect that leads to reduction of fatigue life. Improved welding process and skilled welders can reduce LOP defect to certain extent but does not eliminate it completely. Moreover it increases the time required to fabricate the joint, therefore it is necessary to have an alternative, which can enhance the fatigue life of a joint with a LOP defect. The present paper aims to improve the fatigue life of a load-carrying cruciform fillet welded joint, subjected to high cycle fatigue, having a 100% LOP defect and failing from weld root, by optimizing the weld geometry. In the process of optimization the weld flank angle was varied while keeping the weld leg size constant. A novel convex weld bead profile is developed that accommodates a change in flank angle while keeping the leg size constant. Notch stress approach is used in collaboration with Finite Element Method (FEM) to calculate stress concentration factor (Kt). The detailed guidelines of International Institute of Welding (IIW) recommendations are referred. By using notch stress method, fatigue life in each case of different flank angle is calculated. Finally an optimized weld flank angle is found that would improve the fatigue life of cruciform fillet welded joint.